Multiple Endocrine Neoplasia Type 1 (MEN1) 5′UTR Deletion, in MEN1 Family, Decreases Menin Expression. (15th September 2020) - Kooblall, Kreepa G; Boon, Hannah; Cranston, Treena; Stevenson, Mark; Pagnamenta, Alistair T; Rogers, Angela; Grozinsky‐Glasberg, Simona; Richardson, Tristan; Flanagan, Daniel EH; ,; Taylor, Jenny C; Lines, Kate E; et al.
ABSTRACT: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterized by the occurrence of parathyroid, pancreatic and pituitary tumors, and is due to mutations in the coding region of the MEN1 gene, which encodes menin. We investigated a family with identical twins that had MEN1, with different MEN1 tumors. DNA sequence analysis of the MEN1 coding region had not identified any abnormalities and we hypothesized that deletions and mutations involving the untranslated regions may be involved. Informed consent and venous blood samples were obtained from five family members. Sanger DNA sequencing and multiplex ligation‐dependent probe amplification (MLPA) analyses were performed using leukocyte DNA. This revealed a heterozygous 596bp deletion (Δ596bp) between nucleotides −1087 and −492 upstream of the translation start site, located within the MEN1 5′ untranslated region (UTR), and includes the core promoter and multiple cis‐regulatory regions. To investigate the effects of this 5′UTR deletion on MEN1 promoter activity, we generated luciferase reporter constructs, containing either wild‐type 842bp or mutant 246bp MEN1 promoter, and transfected them into human embryonic kidney HEK293 and pancreatic neuroendocrine tumor BON‐1 cells. This revealed the Δ596bp mutation to result in significant reductions by 37‐fold ( p < 0.0001) and 16‐fold ( p < 0.0001) in luciferase expression in HEK293 and BON‐1 cells, respectively, compared to wild‐type. The effects of this 5′UTR deletion on MEN1 transcription and translation were assessed using qRT‐PCR and Western blot analyses, respectively, of mRNA and protein lysates obtained from Epstein‐Barr‐virus transformed lymphoblastoid cells derived from affected and unaffected individuals. This demonstrated the Δ596bp mutation to result in significant reductions of 84% ( p < 0.05) and 88% ( p < 0.05) in MEN1 mRNA and menin protein, respectively, compared to unaffected individuals. Thus, our results report the first germline MEN1 5′UTR mutation and highlight the importance of investigating UTRs in MEN1 patients who do not have coding region mutations. © 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).